2012
DOI: 10.1039/c2tx00010e
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo studies into the biological activities of 1,10-phenanthroline, 1,10-phenanthroline-5,6-dione and its copper(ii) and silver(i) complexes

Abstract: 1,10-Phenanthroline ( phen, 5), 1,10-phenanthroline-5,6-dione ( phendione, 6), [Cu( phendione) 3 ]-(ClO 4 ) 2 ·4H 2 O (12) and [Ag( phendione) 2 ]ClO 4 (13) are highly active, in vitro, against a range of normal and cancerous mammalian cells, fungal and insect cell lines, with the metal complexes offering a clear enhancement in activity. Cytoselectivity was not observed between the tumorigenic and non-tumorigenic mammalian lines. In in vivo tests, using Galleria mellonella and Swiss mice, all four compounds we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
77
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 60 publications
5
77
0
Order By: Relevance
“…[Ag(6)]ClO 4 was the least active across all of the microbial species, and the activities of the other water-insolubl e Ag(I) complexes were similar to that observed for water-soluble AgNO 3 . In these cases, activity against the fungal pathogen , C. albicans , was greater than that for bacterial pathogens, which is a trend similar to that previously reported for other Ag(I) complexes [5,6,16]. Although there was no clear discriminatory trends observed in activities between Gram-positive (S. aureus and MRSA) and Gram-negati ve (E. coli and P. aeruginosa ) bacteria, most of the complexes, and especially [Ag(4)]ClO 4 ÁMeOH, were more cytotoxic against P. aeruginosa .…”
Section: Antimicrobial Activitysupporting
confidence: 75%
“…[Ag(6)]ClO 4 was the least active across all of the microbial species, and the activities of the other water-insolubl e Ag(I) complexes were similar to that observed for water-soluble AgNO 3 . In these cases, activity against the fungal pathogen , C. albicans , was greater than that for bacterial pathogens, which is a trend similar to that previously reported for other Ag(I) complexes [5,6,16]. Although there was no clear discriminatory trends observed in activities between Gram-positive (S. aureus and MRSA) and Gram-negati ve (E. coli and P. aeruginosa ) bacteria, most of the complexes, and especially [Ag(4)]ClO 4 ÁMeOH, were more cytotoxic against P. aeruginosa .…”
Section: Antimicrobial Activitysupporting
confidence: 75%
“…The only reagent to show good broad spectrum activity against all three bacteria was the dione ligand. This ligand has been previously shown by McCann and co-workers to be very active against several microbes, as well as the yeast Candida Albicans [12,15,16]. Furthermore, when they made silver(I) complexes with the dione ligand, they found that the activity against all the bacteria was increased.…”
Section: Antimicrobial Activitymentioning
confidence: 98%
“…The recent work of McCann and co-workers into the copper(II) and silver(I) complexes of 1,10-phenanthroline and 1,10-phenanthroline-5,6-dione have shown that they are active in vitro anticancer agents against selected cancer cell lines [12][13][14][15][16][17][18][19]. Our interest in the area of therapeutic agents, especially metal-based drugs, is fuelled by the search for new effective medicines for human health, particularly in the areas of cancer therapy and antimicrobials.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the anticancer activity of phendione and its Cu 2+ and Ag + complexes has been studied in a wide spectrum of cell lines, containing not only mouse's and monkeys' cells, but also human-derived cancer cell lines [23,24,26]. In the majority of cases, these complexes exhibit excellent biological activity and represent a class of DNA-targeting compounds capable of inhibiting nucleotide synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting class of ligands is phenanthrolines and substituted derivatives which interact with DNA by aromatic π stacking between the base pairs, both when they are free or coordinated to a metal centre. Among the phenanthroline derivatives, 1,10-phenanthroline-5,6-dione (phendione), displays significant anticancer role with and without a coordinated metal [23,24], whereas it also displays antibacterial and antifungal activity [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%